Characterization of peptides obtained from digests of bovine brain which accelerate structural conversions of the recombinant bovine prion protein. Issue 6 (1st February 2013) - Nokihara, Kiyoshi; Yajima, Shunsuke; Hitara, Akiyoshi; Sogon, Tetsuya; Yasuhara, Tadashi
Abstract : Structural changes of proteins are thought to involve specific protein–peptide interactions, thus we hypothesize that certain peptides may contribute to the conformational change of prion proteins. Hence peptide libraries were constructed from partial digests of bovine brain. Using a recently developed conversion assay method, we have screened peptides responsible for structural conversion. Positive components were identified of which amino acid sequences were elucidated by top‐down sequencing using mass spectrometry. A database search identified a peptide derived from synaptophysin. This peptide was chemically synthesized to confirm acceleration of the structural change of recombinant bovine prion protein. Abstract : ► A peptide library was constructed from enzymatic digests of natural bovine brain. ► Screening was the recently developed methods, the lag‐time of fibril formation. ► MALDI‐TOF‐MS followed by MS/MS of precursor ions revealed peptide sequences. ► The peptide accelerates structural conversions of rbPrP originates synaptophysin. ► Dose‐dependency of the actions was clarified by the synthetic peptide.